Системне прогнозування динаміки взаємозалежних показників енергетичної сфери України - Єфіменко, С.М.; Кваша, Т.К.; Степашко, В.С. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
The modelling of the real economic process by data of Department of economics is executed in the paper. Models for 11 indexes of power sphere of Ukraine with the use of autoregression and multivariate autoregressive models are built. Models of multivariate autoregression showed higher exactness under insufficient amount of experimental data.